2009
DOI: 10.1007/s10900-009-9208-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported Health, Functional Status and Chronic Disease in Community Dwelling Older Adults: Untangling the Role of Demographics

Abstract: Self-reported health, a widely used measure of general health status in population studies, can be affected by certain demographic variables such as gender, race/ethnicity and education. This cross-sectional assessment of the current health status of older adult residents was conducted in an inner-city Houston neighborhood in May, 2007. A survey instrument, with questions on chronic disease prevalence, health limitations/functional status, self-reported subjective health status in addition to demographic data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 17 publications
0
35
1
Order By: Relevance
“…The responses on the scale ranged from 'excellent' to 'poor'. Self-reported health status was found to be affected by demographic variables such as age, gender and geographic location (Banerjee et al 2010). A study conducted in 2013 using the same scale found that over 75% of adults rated their health as moderate or good, with men reporting better health than women.…”
Section: Health Statusmentioning
confidence: 99%
“…The responses on the scale ranged from 'excellent' to 'poor'. Self-reported health status was found to be affected by demographic variables such as age, gender and geographic location (Banerjee et al 2010). A study conducted in 2013 using the same scale found that over 75% of adults rated their health as moderate or good, with men reporting better health than women.…”
Section: Health Statusmentioning
confidence: 99%
“…[1][2][3] This study adds to our understanding of patients' and physicians' reasons for how they rate patient health and their beliefs about improving patient health ratings. We believe this is the first study to explore the congruence of SRH and PRPH based on the patients' and physicians' routine interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Health status was assessed using a single question with 5 response categories presented in a single line (“Poor”, “Fair”, “Good”, “Very Good”, “Excellent”), which we collapsed into a dichotomous variable by grouping those who reported “Poor” or “Fair” health (poorer health) and those who reported “Good”, “Very good” or “Excellent” health (better health) [20]. Although we assessed women’s health status with a widely used measure, this self-assessed measure is subjective [21]. We did not have information on the women’s actual diagnoses, and women with serious, but well-controlled, conditions may have not reported poorer health.…”
Section: Methodsmentioning
confidence: 99%